Gender differences in white matter pathology and mitochondrial dysfunction in Alzheimer’s disease with cerebrovascular disease - Gallart-Palau, Xavier (2018)
Background: Dementia risk in women is higher than in men, but the molecular neuropathology of this gender difference remains poorly defined. In this study, we used unbiased, discovery-driven quantitative proteomics to assess the molecular basis of gender influences on risk of Alzheimer’s disease with cerebrovascular disease (AD + CVD). Results: We detected modulation of several redox proteins in the temporal lobe of AD + CVD subjects, and we observed sex-specific alterations in the white matter (WM) and mitochondria proteomes of female patients. Functional proteomic analysis of AD + CVD brain tissues revealed increased citrullination of arginine and deamidation of glutamine residues of myelin basic protein (MBP) in female which impaired degradation of degenerated MBP and resulted in accumulation of non-functional MBP in WM. Female patients also displayed down-regulation of ATP sub-units and cytochromes, suggesting increased severity of mitochondria impairment in women. Conclusions: Our study demonstrates that gender-linked modulation of white matter and mitochondria proteomes influences neuropathology of the temporal lobe in AD + CVD.